Safety and efficacy of fedratinib, a selective oral inhibitor of Janus kinase‐2 (JAK2), in patients with myelofibrosis and low pretreatment platelet counts. (27th April 2022) - Harrison, Claire N.; Schaap, Nicolaas; Vannucchi, Alessandro M.; Kiladjian, Jean‐Jacques; Passamonti, Francesco; Zweegman, Sonja; Talpaz, Moshe; Verstovsek, Srdan; Rose, Shelonitda; Zhang, Jun; Sy, Oumar; Mesa, Ruben A.
Summary: Fedratinib, an oral Janus kinase‐2 (JAK2) inhibitor, is approved for patients with myelofibrosis (MF) and platelet counts ≥50 × 10 9 /l, based on outcomes from the phase 3, placebo‐controlled JAKARTA trial in JAK‐inhibitor‐naïve MF, and the phase 2, single‐arm JAKARTA2 trial in patients previously treated with ruxolitinib. We evaluated the efficacy and safety of fedratinib 400 mg/day in patients with baseline platelet counts 50 to <100 × 10 9 /l ("Low‐Platelets" cohorts), including 14/96 patients (15%) in JAKARTA and 33/97 (34%) in JAKARTA2. At 24 weeks, spleen response rates were not significantly different between the Low‐Platelets cohort and patients with baseline platelet counts ≥100 × 10 9 /l ("High‐Platelets" cohort), in JAKARTA (36% vs. 49%, respectively; p = 0.37) or JAKARTA2 (36% vs. 28%; p = 0.41). Symptom response rates were also not statistically different between the Low‐ and High‐Platelets cohorts. Fedratinib was generally well‐tolerated in both platelet‐count cohorts. New or worsening thrombocytopaenia was more frequent in the Low‐Platelets (44%) versus the High‐Platelets (9%) cohort, but no serious thrombocytopaenia events occurred. Thrombocytopaenia was typically managed with dose modifications; only 3/48 Low‐Platelets patients discontinued fedratinib due to thrombocytopaenia. These data indicate that fedratinib 400 mg/day is safe and effective in patients with MF and low pretreatment platelet counts, and no initial fedratinib dose adjustment is required for these patients.